A case of carcinoma of the male breast mimicking a mucinous carcinoma of the skin - Sumihisa Imakado; Ryo Masuda (Clinics and Practice, 2012)
The authors report a case of mucinous carcinoma of the male breast firstly diagnosed as a mucinous carcinoma of the skin. The immunohistochemical results of this tumor were as follows: cytokeratin7 (-), gross cystic disease fluid protein 15 (-), p63 (-), estrogen receptor (+), and progesterone receptor (+) for the primary nodule; cytokeratin7 (-), thyroid transcription factor-1 (-), gross cystic disease fluid protein 15 (-), p63 (-), cytokeratin8 (+), cytokeratin18 (+), and cytokeratin20 (+) for the recurrent nodule. The tumor cells had cytokeratin7 (-)/ cytokeratin20 (+) phenotype and it was very unusual for mucinous carcinoma of the breast.